2010
DOI: 10.1111/j.1476-5381.2009.00564.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of peroxisome proliferator‐activated receptor γ agonists on Na+ transport and activity of the kinase SGK1 in epithelial cells from lung and kidney

Abstract: Background and purpose: Peroxisome proliferator-activated receptor g (PPARg) agonists, such as rosiglitazone and pioglitazone, sensitize cells to insulin, and are therefore used to treat type 2 diabetes. However, in some patients, these drugs induce oedema, and the present study tests the hypothesis that this side effect reflects serum and glucocorticoid-inducible kinase 1 (SGK1)-dependent enhancement of epithelia Na + absorption. Experimental approach: Na + absorbing epithelial cells (H441 cells, mpkCCD cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…; Loffing and Korbmacher ; Wilson et al. ). It is therefore important to understand the mechanisms that allow glucocorticoids and insulin to regulate Na + retention within the distal nephron, and earlier work indicates that both hormones act via the serum and glucocorticoid‐inducible kinase 1 (SGK1), a protein kinase that contributes to the control of Na + retention by regulating the abundance of ENaC at the cell surface (De La Rosa et al.…”
Section: Introductionmentioning
confidence: 99%
“…; Loffing and Korbmacher ; Wilson et al. ). It is therefore important to understand the mechanisms that allow glucocorticoids and insulin to regulate Na + retention within the distal nephron, and earlier work indicates that both hormones act via the serum and glucocorticoid‐inducible kinase 1 (SGK1), a protein kinase that contributes to the control of Na + retention by regulating the abundance of ENaC at the cell surface (De La Rosa et al.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study of the respiratory cell line H441, supplemented with dexamethasone, showed no increased phosphorylation of NDRG1 after incubation with insulin (Wilson et al. ). In renal mpkCCD cells, however, the same study showed that the effect of insulin was critically dependent on activation of SGK1 (Wilson et al.…”
Section: Discussionmentioning
confidence: 99%
“…In renal mpkCCD cells, however, the same study showed that the effect of insulin was critically dependent on activation of SGK1 (Wilson et al. ). This suggests different regulatory mechanisms for channel activity between different cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in M1 cells we saw augmentation of Sgk-1 mRNA expression associated with PPAR␥ agonists. However, in mpkCCD cells, PPAR␥ ligands did not increase Sgk-1 mRNA or activity (32,54). Moreover, treatment with RGZ or pioglitazone for 10 days did not significantly alter the opening probability or Fig.…”
Section: Discussionmentioning
confidence: 82%
“…Several studies have suggested that PPAR␥-dependent fluid retention is related to upregulation of ENaC expression and function (11,16); however, to date, no direct transcriptional studies have been performed (47) and investigators have not shown that PPAR␥ ligand treatment is associated with increases in kidney ENaC␥ mRNA or protein expression (11). Furthermore, growing evidence suggests that PPAR␥ agonists do not directly enhance ENaC activity or expression (32,36,45,52,54), and mice with knockdown of ENaC␣ in the collecting duct still develop edema in response to TZD treatment (52). In our studies, we were consistently able to show fluid retention associated with TZDs; however, this was not associated with renal upregulation of ENaC isoform mRNA and protein subunits as previously posited.…”
Section: Discussionmentioning
confidence: 97%